Redistribution and human development: evidence from Europe - Claveria, Oscar (Economics and Business Letters, 2024)
This study examines the relationship between human development and the redistributive effect of taxes and government transfers in 30 European over the period 1990-2021 by means of a fixed-effects panel model. Overall, the analysis suggests that increases in redistribution lead to an increase of development. The coefficient for a one-period lag is also found to be positive and significant, suggesting that the effects of redistributive policies show some persistence. When replicating the experiment for different European regions, the greatest impact of redistributive measures is found in Northern Europe, as opposed to Southern Europe, where the impact on development is not found to be significant.